Pohoval´ni pam˝jatki slov˝jans´kogo času Plisnes´kogo arheologičnogo kompleksu - Filipčuk, Mihajlo (Studia mythologica Slavica, 2014)
This article deals with the burial monuments (middle-late 7th c. - late 10th c.) that are located on the territory of the Plisnesk archaeological complex (Western Ukraine). The materials from two ancient burial grounds with the typical burial ritual and the separate ritual burial places of the Old Slavic sanctuary cult complexes are analysed. Close and distant analogies of burial monuments of Plisnesk are provided.
Keywords: ethnology; etnologija; običaji; customs; burial rituls; pogrebni običaji; archaeology; arheologija; Ukraine; Ukrajina